Mechanical and biological behaviour of porous Ti–SiO2 scaffold for tissue engineering application - Yadav M.K.; Pandey V.; Jyoti; Kumar A.; Mohanta K.; Singh V.K. (My University, 2025)
The present work reports a cost-effective way of fabricating porous Titanium (Ti)/Silica (SiO2) composite scaffold with tailored pore microstructure through powder metallurgy technique, considering the aspect of implants where low bearing load is required with low elastic modulus. Rice husk (RH) powder of different size range was used as fugitive pore former and sucrose was used as a binder which also acted as a pore former. The porosity of the scaffold was controlled by varying the size and amount of space holder. After sintering, the developed composite scaffold was characterized through SEM, XRD, and EDS. Mechanical and biological testing of the scaffold were performed to determine mechanical and biological properties. The resulting scaffolds have the porosity in the range of 15–34%. The addition of silica from RH increased the compressive strength of the scaffold (116–396 MPa). It was also observed that due to the incorporation of pores in Ti matrix there was reduction in Elastic Modulus of the scaffold which is significantly important for Ti based implant materials. Bioactivity of the scaffold was examined by using SBF solution and it was found that the Ti/SiO2 scaffold has ability to form apatite layer. Antibacterial behaviour and biofilm formation on the surface of scaffold were also studied. Obtained result was compared with the properties of natural bone. It was found that the properties of the developed Ti/SiO2 composite scaffolds are similar to that of natural bone and hence can be suitable for orthopaedic application. © 2021 Elsevier Ltd and Techna Group S.r.l.